Correlation of serum Insulin-Like Growth Factor one with acne severity - Saedi Khaleel Fattah; Ali Mozan Dhahir Elethawi (Advanced Medical Journal)
Background and Objectives: Acne is a common chronic inflammatory skin condition; Acne could present as inflammatory or non-inflammatory lesion. Acne can be varied in severity from patient to another, generally, it can present in mild, moderate or severe degree.